A study using patient feedback to predict the effects of quality improvement initiatives in a tertiary care cancer hospital of India - Mohd Anwar Ul Khaliq; Seema Khan; Sumit Yadav (International Journal Of Community Medicine And Public Health, 2026)
Background: Patient feedback is increasingly recognized as an important indicator of healthcare quality and quality improvement (QI), but evidence from tertiary cancer hospitals in India remains limited. Aim was to assess whether patient feedback predicts perceived QI effectiveness and identify key influencing factors. Methods: A descriptive cross-sectional study was conducted among 872 patients at a tertiary care cancer hospital (March-August 2023). Data were collected using a standardised 21-item questionnaire and analysed using descriptive statistics, correlation, and regression analysis. Results: Overall patient satisfaction was high (94%). Patient satisfaction showed a strong positive correlation with perceived QI effectiveness (r=0.701, p